2020
DOI: 10.1038/s41467-020-16044-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of H3K27me3 imprinting in the Sfmbt2 miRNA cluster causes enlargement of cloned mouse placentas

Abstract: Somatic cell nuclear transfer (SCNT) in mammals is an inefficient process that is frequently associated with abnormal phenotypes, especially in placentas. Recent studies demonstrated that mouse SCNT placentas completely lack histone methylation (H3K27me3)-dependent imprinting, but how it affects placental development remains unclear. Here, we provide evidence that the loss of H3K27me3 imprinting is responsible for abnormal placental enlargement and low birth rates following SCNT, through upregulation of imprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 53 publications
3
61
1
Order By: Relevance
“…These epigenetic abnormalities of pre-implantation SCNT embryos are highly correlated with subsequent placenta overgrowth and embryonic lethality (Miri et al, 2013 ; Okae et al, 2014b ; Inoue et al, 2017b ). Intriguingly, the upregulation of clustered miRNAs of Sfmbt2 , one of the H3K27me3-dependent imprinted genes (Matoba et al, 2018 ; Chen et al, 2020 ), has recently been identified as the major cause of placental hyperplasia in SCNT mice (Inoue et al, 2020 ). These observations highlight the crucial function of H3K27me3-imprinted genes in both pre-implantation and postimplantation embryos, although the detailed molecular mechanisms and consequences of intergenerational epigenetic inheritance remain elusive.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…These epigenetic abnormalities of pre-implantation SCNT embryos are highly correlated with subsequent placenta overgrowth and embryonic lethality (Miri et al, 2013 ; Okae et al, 2014b ; Inoue et al, 2017b ). Intriguingly, the upregulation of clustered miRNAs of Sfmbt2 , one of the H3K27me3-dependent imprinted genes (Matoba et al, 2018 ; Chen et al, 2020 ), has recently been identified as the major cause of placental hyperplasia in SCNT mice (Inoue et al, 2020 ). These observations highlight the crucial function of H3K27me3-imprinted genes in both pre-implantation and postimplantation embryos, although the detailed molecular mechanisms and consequences of intergenerational epigenetic inheritance remain elusive.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Interestingly, all the three genes above are included in the 76 genes, which rise the suspect that the defect of H3K27me3 mediated imprinting may cause the abnormality of SCNT placentae. Indeed, many groups proved that loss of H3K27me3-imprinting in SCNT embryos disrupts mouse postimplantation development, and this defect can be detected earliest in blastocyst stage embryos up to now [ 25 , 66 , 67 ]. However, whether this defect exists more earlier in SCNT embryos requires further exploration [ 68 ].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…It is possible that the defects of H3K27me3 reprogramming are relevant to aberrant expression of transposable element during SCNT embryo development. Although restore the normal paternal expression of H3K27me3-imprinting genes ( Sfmbt2 , Gab1 , and Slc38a4 ) in SCNT placentae by maternal knockout unchanged the enlarged placentae state [ 66 ], both correcting the expression of clustered miRNAs within the Sfmbt2 gene and quadruple monoallelic deletion of Sfmbt2 , Jade1 , Gab1 , and Smoc1 ameliorates the placental phenotype, especially Sfmbt2 [ 66 , 67 ].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Although HDACi treatment promotes the epigenetic reprogramming of donor nuclear and pre-implantation embryo development, it is helpless in improving post-implantation development ( Gao R. et al, 2018 ). Recently, it has been reported that loss of maternal imprinting in NT placentas disrupts post-implantation development, and correcting their expression improves placenta development ( Matoba et al, 2018 ; Inoue et al, 2020 ; Wang et al, 2020 ). Abnormal DNA methylation is an epigenetic barrier throughout the NT embryo development ( Teperek and Miyamoto, 2013 ).…”
Section: Introductionmentioning
confidence: 99%